Sectoral Differences in Insurance Penetration Drivers Across Emerging Asia: Evidence from Panel Regressions (The International Research Journal of Management Science, 2025)
Background: Insurance penetration in emerging economies in Asia remains low and uneven, with sectoral differences driven by financial factors and others, highlighting the need to understand the determinants of life and nonlife insurance uptake.Objective: To empirically identify and differentiate the statistically significant and economically meaningful drivers of life vs. nonlife insurance penetration.Method/Design: This study estimated fixed effects regression models on a 68 observations panel data set to understand the life and non-life insurance penetration (calculated as premiums to GDP) across nations.Finding: The main findings of this study note that Life insurance penetration is positively influenced by domestic credit (β = 0.0082), urbanization (β = 0.0487), and internet access (β = 0.00015) but negatively by age dependency (β = –0.0412) and inflation (β = –0.0281), while non-life insurance is driven by imports (β = 0.0085), exports (β = 0.0102), and internet access (β = 0.00006) with inflation negatively influencing (β = –0.0152).Conclusion: Development of the insurance sector in Emerging Asia is not a singular phenomenon and will require distinct strategies based on the economic fundamentals associated with each sector.Implications: All stakeholders in life and non-life insurance industries need to start using sector-specific strategies. These strategies are necessary to realize the enormous insurance potential of the region and enhance economic resilience.